Hubungan Antara Dukungan Keluarga DenganKepatuhan Pasien Low Back Pain (Lbp) DalamJadwal Terapi Akupunktur Di Rumah SakitOrtopedi Prof. Dr. R. Soeharso Surakarta - Romadhon, Nurul Wulan; , Badar Kirwono, SKM, M.Kes; , Kusuma Estu Werdani, SKM., M.Kes (2016)
Low Back Pain (LBP) is the most common pain complaint encountered in the world and in Indonesia.many things influence the discipline in talking therapy by Low Back Pain patient, one of them the family support. The purpose of the research is to get knowledge about the relationship of family support with a discipline Low Back Pain patient in the schedule acupuncture therapy at Ortopedi Prof. Dr. R. Soeharso Surakarta Hospital. The research methodis quantitative in cross sectional of research design. The sample of research is 70 respondents and the research instrument is a questionnaire and checklist. Univariate and bivariate analysis using chi square test with significant level of p<0.05. The research result shows the Low Back Pain patients as follows : emotional support 47 respondents (67.1%), proportional support 48 respondents (68.6%), instrument support 45 respondents (64.3%), informational support 41 respondents (58.6%), discipline in talking therapy 50 respondents (71.4%) and indiscipline in talking therapy 20 respondents (28.6%). There is a relationship among emotional support p-value (0.001), proportional support p-value (0.001), instrument support p-value (0.001), informational support p-value (0.001) with a discipline Low Back Pain patient in the schedule acupuncture therapy at Ortopedi Prof. Dr. R. Soeharso Surakarta Hospital.